A Novel KCNJ2 Mutation Identified in an Autistic Proband Affects the Single Channel Properties of Kir2.1 - Anna Binda; Ilaria Rivolta; Chiara Villa; Elisa Chisci; Massimiliano Beghi; Cesare M. Cornaggia; Roberto Giovannoni; Romina Combi (Frontiers in Cellular Neuroscience, 2018)
Inwardly rectifying potassium channels (Kir) have been historically associated to several cardiovascular disorders. In particular, loss-of-function mutations in the Kir2.1 channel have been reported in cases affected by Andersen-Tawil syndrome while gain-of-function mutations in the same channel cause the short QT3 syndrome. Recently, a missense mutation in Kir2.1, as well as mutations in the Kir4.1, were reported to be involved in autism spectrum disorders (ASDs) suggesting a role of potassium channels in these diseases and introducing the idea of the existence of K+ channel ASDs. Here, we report the identification in an Italian affected family of a novel missense mutation (p.Phe58Ser) in the KCNJ2 gene detected in heterozygosity in a proband affected by autism and borderline for short QT syndrome type 3. The mutation is located in the N-terminal region of the gene coding for the Kir2.1 channel and in particular in a very conserved domain. In vitro assays demonstrated that this mutation results in an increase of the channel conductance and in its open probability. This gain-of-function of the protein is consistent with the autistic phenotype, which is normally associated to an altered neuronal excitability.